The psychosocial impact of assistive device scale: Italian validation in a cohort of nonambulant people with neuromotor disorders. Issue 1 (2nd January 2020) - Tofani, Marco; Candeloro, C.; Sabbadini, M.; Lucibello, L.; Figura, M.; Fabbrini, G.; Galeoto, G.; Castelli, E
ABSTRACT: The importance of adaptive seating system on body structure and function is widely accepted, but its impact on psychosocial aspects needs more consideration by health professionals. This article describes the Italian validation of the Psychosocial Impact of Assistive Device Scale (IT-PIADS) for non-ambulant people with neuromotor disorders. Once agreement has been given by the original authors, the scale was translated and adapted to the Italian culture. The IT-PIADS was administered to different wheelchairs users with heterogeneous diagnosis. The internal consistency and test–retest reliability were examined. Its concurrent validity was evaluated with the Italian version of the WheelCon-M-SF. The IT-PIADS was administered to 87 subjects. Cronbach's α was 0.92 ( p < 0.05), and the test–retest reliability (ICC) for competence, adaptability and self-esteem subscales were 0.96, 0.90, 0.93, respectively. The Pearson correlation coefficient of the IT-PIADS with the WheelCon-M-I-SF scores showed significant data for competence and adaptability subscales. Psychosocial perception on assistive devices can be reliably measure. The IT-PIADS showed good psychometric properties and it is possible to confirm its validity for clinical and research purposes. Nevertheless, before using this measure with greater confidence, further psychometric properties tests of the IT-PIADS are recommended.